Evaluación del uso de distintas métricas de distancia de texto en un algoritmo agregado para la imputación de valores faltantes mediante clasificación - Mena-Arias, José Andrés (Instituto Tecnológico de Costa Rica, 2017)
Nowadays, there is a general problem of missing values in databases around the world, which is caused by several reasons going from hardware malfunctions to nonmandatory fields in forms. Data imputation can be defined as the use of some method to find plausible values for those missing. When the missing value can be inferred from a text value attribute, then the problemcan be seen as a classification algorithms problem where text documents should be organized within categories representing the plausible missing values. It also implies the problem of calculating how similar is a text value with respect to another. Existing literature about solving this kind of problems is extensive, however, during the last 25 years the statistical methods (where similarity functions are applied over vectors of words) have achieved good results in many areas of text mining [38]. Additionally, topic modeling has arisen in the last years as a promising alternative to existing methods by achieving dimensional reduction and incorporating the semantic factor when classifying documents [30]. This project is focused on the evaluation of traditional data representation techniques and similarity metrics (words vectors, Cosine and Jaccard) respect to topic modeling techniques and probability distributions comparison (Latent Dirichlet Allocation and Kullback- Leibler Divergence). An statistical analysis is applied to the results obtained after running several experiments that involved the mentioned metrics, both individually and combined, to classify data sets of text documents. At a high level, the results show that the accuracy scores achieved by using document representations obtained thought Latent Dirichlet Allocation, combined with the relative entropy metric, were statically similar to the ones obtained by using traditional text classification techniques. The topics modeling manages to abstract thousands of words in less than 60 topics for the main set of experiments. The results also highlight cons, improvement areas and potential scenarios where such models could achieve a better performance.
Proyecto de Graduación (Maestría en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2017.
Keywords: Bases de Datos; Métodos; Categorías; Modelado; Dirichlet Latente; Research Subject Categories::TECHNOLOGY::Information technology::Computer engineering